Human–wildlife coexistence: attitudes and behavioural intentions towards predators in the Maasai Mara, Kenya. Issue 3 (27th May 2020) - Broekhuis, Femke; Kaelo, Michael; Sakat, Dominic Kantai; Elliot, Nicholas B.
Abstract: Living alongside predators can entail substantial costs both in terms of livelihoods and personal safety. Negative interactions with predators can lead to negative attitudes and behavioural intentions such as retaliatory or pre-emptive killing. As a result, conservation strategies are increasingly adopting human–wildlife coexistence approaches aimed at minimizing the costs associated with living with predators by providing direct or indirect benefits. This is done in the hope that people will foster positive attitudes and behavioural intentions towards predators. However, people's attitudes and their behavioural intentions are not necessarily linked, and both need to be understood for conservation actions to be effective. We conducted 747 semi-structured interviews with community members in the Maasai Mara, Kenya, to determine which factors influenced people's attitudes and behavioural intentions towards predators and whether the two were linked. Most interviewees (57.52%) had a positive attitude towards predators as measured by their assertion that people, livestock and predators should coexist. Their attitude was dependent on benefits, occupation, conservancy membership and perceived community ownership of predators, but was not influenced by the costs of livestock depredation. Most respondents who were members of a conservancy had positive attitudes towards predators but this differed by conservancy, suggesting that, in addition to benefits, conservation politics could influence attitudes. In total, 10.3% of respondents said that they would kill a predator if it killed their livestock. This behavioural intention was only influenced by the respondent's attitude. Understanding the factors that influence attitudes and behavioural intentions will aid future management and coexistence strategies.